ALAT PENANGKAP BAU DAN UAP BAHAN KIMIA BERBAHAYA UNTUK MELINDUNGI PEKERJA KERAJINAN FIBERGLASS DI PRAMBANAN DIY - Sahroni, Imam; Zuhrufa, Zulfa; Nisaa, Choirun; Sajidah, Happy Bunga Nasyirahul (Program Kreativitas Mahasiswa - Teknologi, 2013)
In this paper, preparation of technology and its utilization as trapped function of dangerous odor and vapor in âfiberglassâ art is presented. Trapped technology was prepared by using blower pump, pipa PVC, and n-hexene as liquid trapping. Fiberglass batter was sipped from pump through pipa PVC. Dangerous compound from fiberglass was trapped by liquid trapping in closed system. Dangerous compound characterization in n-hexane was performed by GC-MS analysis. From the result, it is concluded that trapped technology can trap fiveteen (15) dangerous compund from fiberglass batter with five (5) dominant peakes. There are 2-methylpentane, methylbenzena, methylcyclohexene, 1-oktene, and cyclohexene.